Pilot-scale production and physicochemical properties of mycelium-based materials and diversity assessment of a fungal biobank - Rajaruthnam, Sunthuri (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.